Cavidad idiopática de Stafne: características y consideraciones imagenológicas. Una revisión - Cruces Valdivia, Alexandra Gabriela (2021)
In 1942, Dr. Edward Stafne presented 35 cases of asymptomatic, clearly defined, round or ovoid radiolucencies occurring near the angle of the mandible, with a greater incidence below the lower dental canal, between the mandibular angle and the roots of the first lower molar, which he referred to as a bone defect. This bone defect later became known by other names. Clinically, Stafne’s idiopathic bone cavity (SIBC) is asymptomatic, is usually not palpated intraorally and has no present extraoral signs. Thus, in most cases it is an accidental radiological finding, which appears as a delimited, elliptical, or rounded radiolucent image, with a diameter ranging from 1 to 3 cm, and delimited by osteocondensation in the anteroinferior limits. According to the location of the findings, they are classified as; anterior, posterior and branch. This entity should be considered as a variant of normality requiring differential diagnosis to achieve an accurate diagnosis. The present review provides information on the history, and general and radiographic characteristics of SIBC to facilitate diagnosis when presented with this type of findings.